A preliminary investigation of China Ginger and Kuching Local Ginger species: Oil extracts and synthesis towards potential greener insect repellent - Wong, Fong Fei; Mohammad Omar, Abdullah; Hii, Yik Rong; Chang, Sze Ying; Noraziah, Abdul Wahab; Hafizah, Abdul Halim Yun; Mohd Zaidi, Jaafar; Agi, Augustine Aja (Elsevier B.V., 2023)
Ginger essential oil (Zingiber officinale) is the volatile oil extracted from ginger rhizome. Compared to chemical synthetic repellent, green insect (in particular mosquito) repellent would be favoured by the public as it is environmentally friendly and does not cause harm to the human’s health. The focus of this study is on the comparison study between China Ginger and Kuching Local Ginger essential oil aim towards utilization as the greener mosquito repellent. In this study, the ginger essential oils are extracted greener method i.e. via hydro distillation process for 7 h. The percentage oil yield for China and Kuching Local Ginger are 0.158 wt% and 0.264 wt%, respectively. The extracted ginger essential oils are further subject to Fourier Transform Infrared Spectroscopy (FTIR) and Gas Chromatography- Mass spectrometry (GC-MS) analysis. Based on the FTIR spectrum graph generated, both types of ginger essential oils essentially having the similar function groups including phenolic compounds, alcohol primer, alkena methyl group, aromatic compound, carbonyl compound, carboxylic acid, hydroxyl group. From the GC-MS results it revealed that the most abundant chemical constituents presented in both China Gniger and Kuching Local Ginger essential are: α-Zingiberene (7.88% and 7.03%), α-Curcumene (6.04% and 6.49%), α-Citral or Genarial (3.81% and 7.86%), β-Bisabolene (3.06% and 4.62%), β-Sesquiphellandrene (5.83% and 5.95%), β-Sesquisabinene (0.07% and 0.51%), β-Selinenol (3.97% and 2.26%), Zingiberenol (5.16% and 1.64%), [6]-Shogaol (0.33% and 0.23%), trans-Sesquisabinene hydrate (1.72% and 2.87%), trans-Geranylgeraniol (3.51% and 2.81%), Camphene (1.17% and 0.56%), Eucalyptol (2.68% and 1.81%), Citronellol (1.76% and 1.55%), Neral (2.82% and 6.03%), and Geraniol (1.62% and 2.29%) respectively. Kuching Local Ginger essential oil is found marginally superior insect repellent characteristics due to its higher monoterpene compounds in the essential oil.